DIAGNOSTIC CRITERIA OF GENETIC MARKERS OF INCREASED RISK OF DEVELOPMENT OF POST-TRAUMATIC STRESS DISORDER. - Верголяс, Майя; Леонов, Юрій; Верголяс, Олександр; Нечипоренко, С.Г.; Верголяс, О.І. (SWorldJournal, 2025)
The consequence of large-scale military operations in Ukraine is a significant complex negative impact of social, economic, environmental, sanitary-epidemiological and psychological effects. The complex impact of factors is the main cause of stress-associ